2008
DOI: 10.1016/j.cub.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Sleep: Dozy Worms and Sleepy Flies

Abstract: Recent work on quiescent states in Caenorhabditis elegans suggests that worms exhibit behaviours reminiscent of satiety and sleep in mammals. At a molecular level, signalling through the EGF receptor and protein kinase G promotes quiescent states in both worms and flies, suggesting conserved mechanisms for sleep-like behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…In recent years, an important advance in sleep research has been the identification of a sleep state in non-mammalian model systems: namely, the fruit fly ( Drosophila melanogaster ) [2022], the zebrafish ( Danio rerio ) [2325] and, most recently, the nematode ( Caenorhabditis elegans ) [26] (see also [2729]). Crucial to the identification of sleep in these model systems has been the use of behavioral rather than electrophysiological criteria to define the sleep state.…”
Section: Model Systems For the Study Of Sleepmentioning
confidence: 99%
“…In recent years, an important advance in sleep research has been the identification of a sleep state in non-mammalian model systems: namely, the fruit fly ( Drosophila melanogaster ) [2022], the zebrafish ( Danio rerio ) [2325] and, most recently, the nematode ( Caenorhabditis elegans ) [26] (see also [2729]). Crucial to the identification of sleep in these model systems has been the use of behavioral rather than electrophysiological criteria to define the sleep state.…”
Section: Model Systems For the Study Of Sleepmentioning
confidence: 99%
“…C. elegans ($300 neurons) has a quiescent behavioral state during a period called lethargus. [260][261][262] It occurs before each of the four molts and exhibits some aspects of sleep, including higher arousal thresholds and a homeostatic response to mechanical stimulation during lethargus (specifically, an augmented quiescence after stimulation). 260 The periods of lethargus involve alterations of the worm's nervous system, suggesting that lethargus evolved to accommodate specific requirements of such alterations.…”
Section: Protein Fragments and The Size Of A Nervous Systemmentioning
confidence: 99%
“…[260][261][262][263][264] The FG hypothesis predicts higher levels of specific protease-generated protein fragments in some or most C. elegans neurons (and possibly in other cell types as well) shortly before lethargus. If the FG hypothesis proves relevant to the causation and function of sleep in mammals, the resulting understanding could be ''turned around'' by asking whether the lethargus in C. elegans involves the generation and degradation of specific fragments and the remodeling of protein complexes after fragments' removal, and whether these processes are the molecular cause of lethargus.…”
Section: Protein Fragments and The Size Of A Nervous Systemmentioning
confidence: 99%
“…Further, while organisms such as neurospora and plants show daily cycles of activity, a definition of sleep has not been extended to these species, although a recent study has revealed a sleep-like state in Caenorhabditis elegans called lethargus [ 36 ]. Common sleep pathways in these organisms have involved dopamine [ 37 , 38 ], cyclic AMP response element-binding protein (CREB) [ 39 , 40 ], voltage-dependent potassium channels [ 33 , 41 ], gamma-aminobutyric acid (GABA) [ 42 ], and the epidermal growth factor [ 43 , 44 ].…”
Section: Sleep In Other Organismsmentioning
confidence: 99%